Pengaplikasian Teknik Distressed dalam Visualisasi Rebel - Hasya Zalfa Harsan; Fendi Nofrian; Desra Imelda; Fadri Rahmat (INDO PUBLISHING, 2026)
Fashion is a form of visual non-verbal communication that conveys meaning regarding the wearer's identity, emotion, and ideological values. This meaning is constructed not only through silhouettes but also through material processing using textile manipulation techniques. The creation of this work aims to develop a clothing collection themed around resistance by exploring distressed manipulation techniques. This design concept shifts the psychological analogy of psychological distress, such as slashing, burning, puncturing, and other destructive acts, into a controlled creative process to express a rebellious attitude. As a conceptual balance as well as a preservation of cultural roots, this design integrates Silungkang songket with the bunga pecah lapan motif. The creation method of this work progresses through the stages of idea exploration, design planning, and final artwork execution. The ultimate result of this design consists of three collections: a ready-to-wear collection titled